Nilai-Nilai Budaya dalam Gurindam Tunjuk Ajar Melayu Karya Tenas Effendy - Rahayu, Sri; Alber, Alber (GERAM, 2019)
In the era of globalization there have been many changes and shifts in cultural values ​​within Malay society, causing neglected gurindam and other folk literature. The Malay community is now more interested in reading social media than reading literature, especially the younger generation. The younger generation is increasingly distant from the traditions espoused especially if it is associated with degradation and moral decadence that are very different from those of young people in the past. Therefore, the purpose of this study is to analyze and interpret the cultural values ​​in folk literature, especially those that are exemplary to the younger generation. This needs to be examined as a form of contribution to the development of mental and character building. This research is descriptive with content analysis method. The data of this study are sourced from the 2013 book Teachings of Teachings by Tenas Effendy. The data studied is documented by means of reading, further recording is concluded and grouped based on the cultural values ​​contained therein. Based on the observations of the author, the Malay teaching point in the Tenind Effendy workshops contributed to cultural values ​​including responsibility, obedience, giving advice, respect, love and loyalty.